2023
DOI: 10.1111/jdv.19286
|View full text |Cite
|
Sign up to set email alerts
|

Hidradenitis suppurativa presents a methylome dysregulation capable to explain the pro‐inflammatory microenvironment: Are these DNA methylations potential therapeutic targets?

Abstract: BackgroundHidradenitis suppurativa (HS) is a chronic, systemic, inflammatory skin condition with elusive pathogenesis that affects therapeutic intervention directly.ObjectiveTo characterize epigenetic variations in cytokines genes contributing to HS.MethodsEpigenome‐wide DNA methylation profiling with the Illumina Epic array was performed on blood DNA samples from 24 HS patients and 24 age‐ and sex‐matched controls to explore DNA methylation changes in cytokine genes.ResultsWe identified 170 cytokine genes inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 76 publications
0
5
0
Order By: Relevance
“…Recent studies identified microRNA, cytochrome, and cytokine gene methylation dysregulations associated with HS. [ 65 66 67 68 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies identified microRNA, cytochrome, and cytokine gene methylation dysregulations associated with HS. [ 65 66 67 68 ]…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic studies highlighted a dysmethylation background for HS patients, which disrupts cell aging and functionality, inflammatory response, and drug metabolism, consequently altering the cutaneous immune system–microbiome homeostasis [ 6 , 7 , 8 , 9 ]. Thus, a more detailed understanding of cutaneous dysbiosis occurrence is of paramount importance to prevent disease progression and innovate a curative intervention instead of merely treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The immunopathology of HS includes genetic factors and environmental factors including obesity and smoking (both active and passive) and various epigenetic alterations have been reported. [6][7][8][9][10][11][12] Studies of various large-scale exomes and candidate γ-secretase gene mutations have been reported to have identified ~80 different gene variants involved in HS disease aetiology across the globe, 13,14 as well as genetic heterogeneity. 15 Most variants were detected in patients with a family history of HS, but a small number were also found in sporadic cases.…”
Section: Introductionmentioning
confidence: 99%